PENGARUH KEPERCAYAAN DAN KEMUDAHAN PENGGUNAAN TERHADAP LOYALITAS PENGGUNA DANA DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI: STUDI PADA MAHASISWA DI KOTA PALANGKA RAYA - Astrid, Astrid; Kristinae, Vivy; Mahrita, Ani; Syamsudin, Achmad (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
DANA is one of the most popular e-wallet in Indonesia, with over 190 million users. This study aims to examine the influence of trust and perceived ease of use on user loyalty, with customer satisfaction serving as a mediating variable. The research employed a quantitative survey design with a total of 100 respondents, and data were analyzed using PLS-SEM through SmartPLS 4.0. The findings reveal that trust has a positive and significant effect on user loyalty toward the DANA application, whereas perceived ease of use shows a positive but insignificant effect on user loyalty. Nonetheless, both trust and perceived ease of use exert a positive influence on customer satisfaction, which in turn mediates and strengthens their relationship with user loyalty. These results highlight that trust and customer satisfaction are essential determinants in fostering long-term loyalty among DANA application users.